The Effect of Audio-Visual Education on Early Detection of Cervical Cancer on Motivation for Visual Acetic Acid Inspection Examinations Among Women of Childbearing Age - Pryati Rihi; Erlin Oktavia Tunliu; Fon, Maria Anjelina (Journal of Tropical Diseases and Health Science, 2024)
Cervical cancer is a type of malignant cancer in women which globally ranks fourth in threatening women's health with the impact of death. Audio-visual education for early detection of cervical cancer is a major factor in motivating VIA examinations in women of childbearing age. Objective: This study was to determine the effect of audio-visual education for early detection of cervical cancer on the motivation for VIA examinations in women of childbearing age in the Pasir Panjang Community Health Center work area. Method: This study used a pre-experimental design with one group pre-test post-test design. By using a purposive sampling technique, 79 respondents were recruited as samples. Data collection tools used questionnaires and audio-visual media. The research variables were audio-visual education for early detection of cervical cancer (independent variable) and motivation for VIA examination (dependent variable). Data analysis was carried out using the Wilxocon test. Results The results of the statistical test analysis obtained a p-value of 0.000 <0.05 which indicated that there was an effect of audio-visual education for early detection of cervical cancer on the motivation for VIA examinations in women of childbearing age in the Pasir Panjang Community Health Center work area. Conclusion: Providing audio-visual education for early detection of cervical cancer can increase the motivation of women of childbearing age to undergo VIA examinations.